JOB SATISFACTION OF AGRICULTURAL EXTENSION WORKERS IN SULAYMANIYAH GOVERNORATE AND ITS RELATIONSHIP WITH SOME VARIABLES - Tablo; Mohammed Omer Mohammed Sakina (University of Thi-Qar Journal of agricultural research, 2025)
This study aimed to identify the job satisfaction of agricultural extension workers in Sulaymaniyah governorate in general, and in each fields of (relationship with colleagues, Relationship with superiors, salaries and incentives, work policy, annual and increment promotions, nature of the work, work environment). The research population involved all extension workers in the agricultural extension organization, they were (126)* agricultural extension workers, after excluding 20 respondents from the exploratory sample, the research sample became (106) respondents representing the research community. The data was collected through personal interviews face to face; questionnaire was prepared for this purpose. To confirm the validity the questionnaire was reviewed by some experts of agricultural extension. The reliability coefficient was evaluated by (Cronbach’s Alpha) coefficient. The results appeared that the level of job satisfaction medium tends to low, and fields of (the relationship with colleagues and superior) occupied the first and second rank, and the field of (salaries and incentives with promotion and increment) occupied sixth and final. The results showed there is a significant difference in job satisfaction according to (service duration, attitude towards agricultural extension, problem solving ability). While no significant differences according to (age, gender, provenance, current residence, academic achievement, type of residence, distance the residence from the workplace, work place, previous training). The study recommended creating conditions and improving a suitable work environment based on human relations in all areas of job satisfaction, focusing on addressing, improving and reviewing all matters related to the material and moral benefits of employees, and increasing awareness and positive attitudes towards agricultural guidance as an important factor in increasing job satisfaction